Cracking Properties of Warm Mix Asphalts Containing Reclaimed Asphalt Pavement and Recycling Agents under Different Loading Modes. (20th September 2021) - Yousefi, Afshar A.; Sobhi, Saeid; Aliha, M.R.M.; Pirmohammad, Sadjad; Haghshenas, Hamzeh F.
Highlights: The incorporation of RAP reduced the fracture toughness and energy at −15 °C while it resulted in an increase in these fracture properties at 25 °C under different loading modes. The use of recycling agents increased the fracture toughness and energy at subzero-temperature under different loading modes. The fracture toughness and energy of mixtures at mid-temperature decreased by addition of recycling agents. The efficacy of recycling agents on the fracture properties depending on the type and origin of recycling agents. Abstract: This paper aims to evaluate the influence of two recycling agents (RAs) on the cracking behavior of warm mix asphalt (WMA) containing up to 50% reclaimed asphalt pavement (RAP). Two chemically different types of recycling agents, namely aromatic extracts and triglycerides/fatty acids, together with a WMA additive (Sasobit®) were introduced to the mixture. A hot mix asphalt (HMA) mixture (as control mixture) and seven WMA mixtures containing three different dosages of RAP (0, 25, and 50%) and modified by two RAs were prepared. The fracture toughness and energy of the above-mentioned asphalt mixtures were evaluated under pure modes of I and II and mixed mode I/II using the semi-circular bending (SCB) test at mid and subzero temperatures. The results indicated that the cracking resistance of the WMA mixtures without RAP is better than the HMA mixtures under different modes of fracture regardless of the temperature (−15 °C and 25 °C). In addition, at −15 °C, the presence of RAP in the WMA mixtures reduced the fracture toughness and energy while at 25 °C, it results in an increase in fracture toughness and energy. Moreover, the addition of RAs to the WMA mixtures containing RAP increased the fracture toughness and energy at −15 °C. Although RAs decreased the fracture toughness and energy of the RAP blended WMA mixtures at mid-temperature, the performance of these mixtures was better than the HMA mixture.